Investigation of the Efficacy of Agomelatine on Depression-like Behaviors in an Experimental Abortion Model - Ozdede, Mehmet Ridvan; Pervin, Mehtap; Sayin, Orhan; Bozyil, Ahmed Sait; Batmaz, Husna; Yasar, Abdullah; Kacar, Emine (Wiley, 2025)
[Abstract Not Available]
Keywords: Abortion; Agomelatine; Forced swimming test; Pregnancy; Rat